Pragmatic Study of Display Advertisements in Harian Rakyat Aceh - Faisal, Faisal; Fauzia, Siti Naila; Haris, A (International Conference on Multidisciplinary Research, 2020)
This study aims to describe the role of pragmatics in delivering the meaning of print advertisements in the Harian Rakyat Aceh newspaper. This research used a qualitative approach. The data was analyzed using a pragmatic approach. The data of this research were advertisements published in the Harian Rakyat Aceh newspaper in January 2019. The data were identified, classified, analyzed, described, and summarized. The results showed that all the advertisements used pragmatic power to convey information. The pragmatic power that appears is the presupposition and context of the advertisement. The presupposition arises from the main trademark of a product or product brand that has been popular in society. Context refers to images, letter shapes, colours, and motives of images and letters in advertisements published in the Harian Rakyat Aceh newspaper. Keywords: pragmatics, advertisement, Harian Rakyat Aceh